К 90-летию со дня рождения Андрея Петровича Таркова - Дубянский, Александр Игоревич; Надёжка, Людмила Ивановн; Силкина, Татьяна Борисовна (Вестник ВГУ. Серия: Геология, 2020)
К 90-летию со дня рождения Андрея Петровича Таркова